The Influence of Community Participation and Transparency on Village Fund Accountability Through Technology Moderation - Shelma Desinta Dukalaa; Nur Anita Chandra Putry; Fuadhillah Kirana Putri (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to examine the influence of community participation and transparency on village fund accountability through the moderation of technology. The research involved 84 village government officials in the Yogyakarta region, aged at least 18 years with a minimum of one year of service. Primary data were collected through questionnaires distributed directly to respondents using the convenience sampling method and analyzed using descriptive statistics with the assistance of IBM SPSS version 25. The results shows that community participation and transparency have a positive and significant influence on village fund accountability. Furthermore, technology has been proven to strengthen the impact of community participation and transparency on village fund accountability. This study contributes to the literature on village fund management by emphasizing the importance of community participation and transparency in enhancing accountability. Additionally, it highlights the role of technology moderation as an effective strategy to strengthen governance in the digital era.